An Effect of Using Group Investigation Method to Improving Critical Thinking Skill - Yohana Puspita Dewi; Purna Wiratno; Destia Herlisya (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
Students' critical thinking ability can be enhanced through an effective learning process. To achieve this, the learning process must be designed to engage students in the classroom actively. The effort to achieve these results involves improving the quality of learning through effective teaching materials. Learning involves more than just acquiring information from lecturers; it encompasses various activities and actions to achieve better student learning outcomes. For instance, providing tasks that stimulate students to think critically, incorporating methods and learning models into the teaching process, is essential. The learning process is fundamentally a teaching-learning process that underscores the significance of experiential learning to gain valuable insights. This research aims to identify the process and outcomes of implementing the group investigation learning model to enhance critical thinking skills. Students' critical thinking is crucial as, during the learning process, students formulate ideas about the problems presented in their studies. Some students face challenges in thinking creatively when learning in English. They struggle to express their ideas, lack vocabulary, and find it challenging to generate ideas to solve problems when asked to discuss topics in English. Examples of these topics include educational issues and the impact of technology on students.